Recording, mapping, and visualising soundscapes in Singapore - Goh, Jessie (Nanyang Technological University, 2023)
According to the definition of ‘soundscape’ in the international standard for soundscapes, soundscapes are meant to be experienced in context. In other words, soundscape attributes will then depend on human perception and may differ for different settings. Part 3 of the International Standard ISO 12913:3-2019 defines a soundscape perceptual model with two perception attributes, “Pleasantness” and “Eventfulness”, but does not provide any reference soundscapes that correspond to these attributes. Therefore, it is crucial to record accompanying audio-visual data of these characteristic soundscapes to create a comprehensive reference database for future soundscape research. As such, we produced a database of 62 characteristic Singapore soundscapes into an audio-visual database. This was done first by verifying our recording equipment using an automated calibration process against previously verified set ups, before recording at least 30 minutes of audio-visual data of each soundscape. Soundscape recordings consist of a 360-degree video, binaural audio, ambisonics audio, and sound pressure levels. These soundscapes were then visualised on an interactive map on a web application. The development of an admin interface is suggested for future work.